Socio-Emotional Competencies and School Performance in Adolescence: What Role for School Adjustment? - Mella, Nathalie; Pansu, Pascal; Batruch, Anatolia; Bressan, Marco; Bressoux, Pascal; Brown, Genavee; Butera, Fabrizio; Cherbonnier, Anthony; Darnon, Céline; Demolliens, Marie; De Place, Anne-Laure; Huguet, Pascal; et al. (Frontiers in Psychology, 2021)
There is growing evidence in the literature of positive relationships between socio-emotional competencies and school performance. Several hypotheses have been used to explain how these variables may be related to school performance. In this paper, we explored the role of various school adjustment variables in the relationship between interpersonal socio-emotional competencies and school grades, using a weighted network approach. This network approach allowed us to analyse the structure of interrelations between each variable, pointing to both central and mediatory school and socio-emotional variables within the network. Self-reported data from around 3'400 French vocational high school students were examined. This data included a set of interpersonal socio-emotional competencies (cognitive and affective empathy, socio-emotional behaviours and collective orientation), school adjustment measures (adaptation to the institution, school anxiety, self-regulation at school, and perceived self-competence at school) as well as grades in mathematics and French language. The results showed that self-regulation at school weighted the most strongly on the whole network, and was the most important mediatory pathway. More specifically, self-regulation mediated the relationships between interpersonal socio-emotional competencies and school grades.